LINGUISTICS IN THE ANTHROPOCENTRIC PARADIGM METHODOLOGICAL FOUNDATIONS OF SCIENCE - Solijonov Mukhammadjon; Kholiqova Lutfiya (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The purpose of the article is to discuss and find out some features of modern linguistics. Moreover, the article illustrates the theoretical foundations of the study of culture through language.